Cover Image, Volume 87, Issue 2. (August 2017) - Schaefers, J.; Cools, M.; De Waele, K.; Gies, I.; Beauloye, V.; Lysy, P.; Francois, I.; Beckers, D.; De Schepper, J.
Abstract : The cover image, by J. Schaefers et al., is based on the Original Article Clinical presentation and outcome of children with central diabetes insipidus associated with a self‐limited or transient pituitary stalk thickening, diagnosed as infundibuloneurohypophysitis, DOI:10.1111/cen.13362 .